Impulse Control Disorders in Parkinson's Disease: Epidemiology, Pathogenesis and Therapeutic Strategies - Zhang, Jun-Fang; Wang, Xi-Xi; Feng, Ya; Fekete, Robert; Jankovic, Joseph; Wu, Yun-Cheng (Frontiers in Psychiatry, 2021)
Impulse control disorders (ICDs) in Parkinson’s disease (PD) are aberrant behavior such as pathological gambling, hypersexuality, binge eating and compulsive buying, which typically occur as a result of dopaminergic therapy. Numerous studies have focused on the broad spectrum of ICDs-related behaviors and their tremendous impact on patients and their family members. Recent advances have improved our understanding of ICDs. In this review, we discuss the epidemiology, pathogenesis and treatment of ICDs in the setting of PD.